2007
DOI: 10.1107/s1600536807035040
|View full text |Cite
|
Sign up to set email alerts
|

catena-Poly[[(μ-4,4′-bipyridine-κ2N:N′)bis[aqua(dimethylformamide-κO)copper(II)]]-di-μ-terephthalato-κ4O1:O4]

Abstract: The title coordination polymer, [Cu2(C8H4O4)2(C10H8N2)(C3H7NO)2(H2O)2]n, adopts a ladder structure in which terephthalate functions as the rails and bipyridine, lying on inversion centres, as the rungs. The Cu atom is also coordinated by water and dimethylformamide molecules in a square‐pyramidal environment. Hydrogen bonds link the ladders into a three‐dimensional network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…3) and c g ···c g distance (Janiak, 2000) is 4.17 Å. The similar supramolecular synthons R 2 2 (10) and R 2 2 (12) (Bernstein et al, 1995) have been also observed in crystal structure of one dinuclear complex (Valigura et al, 2006) and several polymeric complexes (Abourahma et al, 2002;Burrows et al, 2008;Cao et al, 2008;Korabik et al, 2011;Maharramov et al, 2012;Vaskova et al, 2011;Xu et al, 2007;Yamada et al, 1998). The crystal packing of 1 is shown in Fig.…”
Section: Resultsmentioning
confidence: 74%
“…3) and c g ···c g distance (Janiak, 2000) is 4.17 Å. The similar supramolecular synthons R 2 2 (10) and R 2 2 (12) (Bernstein et al, 1995) have been also observed in crystal structure of one dinuclear complex (Valigura et al, 2006) and several polymeric complexes (Abourahma et al, 2002;Burrows et al, 2008;Cao et al, 2008;Korabik et al, 2011;Maharramov et al, 2012;Vaskova et al, 2011;Xu et al, 2007;Yamada et al, 1998). The crystal packing of 1 is shown in Fig.…”
Section: Resultsmentioning
confidence: 74%